2019
DOI: 10.1186/s13287-019-1215-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with hyaluronan matrix and miRNA cargo as contributors for in vitro potential of mesenchymal stem cell-derived extracellular vesicles in a model of human osteoarthritic synoviocytes

Abstract: Background Osteoarthritis (OA) is the most prevalent joint disease, and to date, no options for effective tissue repair and restoration are available. With the aim of developing new therapies, the impact of mesenchymal stem cells (MSCs) has been explored, and the efficacy of MSCs started to be deciphered. A strong paracrine capacity relying on both secreted and vesicle-embedded (EVs) protein or nucleic acid-based factors has been proposed as the principal mechanism that contributes to tissue repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 87 publications
8
73
0
Order By: Relevance
“…Shuttling of select-miRNAs in microvesicles and delivery to target cells has been observed in human bone-marrow MSCs [7]. A similar phenomenon was also recently reported in ASC, where exosome-shuttled miRNAs were found to reduce the expression of pro-inflammatory cytokines and chemokines in an in vitro model of chronic inflammation [8]. Therefore, the therapeutic potency of ASC is likely to be linked in part to microRNA expression [5].…”
Section: Introductionsupporting
confidence: 55%
“…Shuttling of select-miRNAs in microvesicles and delivery to target cells has been observed in human bone-marrow MSCs [7]. A similar phenomenon was also recently reported in ASC, where exosome-shuttled miRNAs were found to reduce the expression of pro-inflammatory cytokines and chemokines in an in vitro model of chronic inflammation [8]. Therefore, the therapeutic potency of ASC is likely to be linked in part to microRNA expression [5].…”
Section: Introductionsupporting
confidence: 55%
“…CXCL8 showed significant contractions, suggesting that EVs regulates inflammation through the CREB pathway. In summary, AD-MSCs EVs decreased the expression of pro-inflammatory cytokines and chemokines in the chronic FLS inflammatory model [86]. Moreover, AD-MSCs EVs down-regulated β-galactosidase activity and the accumulation of γH2AX foci which was associated with senescence.…”
Section: The Therapeutic Effects Of Evs From Ad-mscsmentioning
confidence: 80%
“…Our literature search revealed that most studies focused on the therapeutic aspect of miRNAs of MSC-derived EVs. Only a few studies made the data of their miRNA arrays publicly available [32][33][34]. Additionally, the role of MSC-derived miRNAs in cancer biology has been discussed and investigated by other groups.…”
Section: Mirna Profilementioning
confidence: 99%
“…Even here, however, only few groups made all collected data available for secondary analysis. In the case of AT-MSCs, one group has investigated the role of AT-MSC-derived EVs in the development and treatment of osteoarthritis [32,33]. In both publications, the raw data of the miRNA array were made available by the authors.…”
Section: Mirna Profilementioning
confidence: 99%